The Relationship Between Market Orientation And Export Performance: The Mediation Impact Of Export Marketing Management Competency And The Moderating Effect Of Environmental Factors - Sefnedi, Sefnedi (2007)
Sektor pembuatan berperanan besar ke atas ekspot Indonesia dan menyumbang secara signifikan kepada keluaran dalam negara kasar (KDNK).